2013
DOI: 10.1007/s10482-013-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium ulcerans isolates from humans and dogs: fibrinogen, fibronectin and collagen-binding, antimicrobial and PFGE profiles

Abstract: Corynebacterium ulcerans has been increasingly isolated as an emerging zoonotic agent of diphtheria and other infections from companion animals. Since pets are able to act as symptomless carriers, it is also essential to identify virulence potential for humans of these isolates. In this work the ability of C. ulcerans to bind to fibrinogen (Fbg), fibronectin (Fn) and Type I collagen as well the genetic relationship among strains isolated from human and asymptomatic dogs in Rio de Janeiro (Brazil) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Many pathogens colonize human tissues or evade immune mechanisms of bacterial clearance exploiting extracellular matrix and/or plasma proteins to colonize human tissues or to evade immune mechanisms for clearance of bacteria (Simpson-Louredo et al, 2014). Sabbadini et al (2010) suggested that the conversion of fibrinogen to fibrin may be connected to pseudomembrane formation, since differences in the abilities to bind and convert fibrinogen may partially explain differences in the extent of pseudomembrane formation during diphtheria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pathogens colonize human tissues or evade immune mechanisms of bacterial clearance exploiting extracellular matrix and/or plasma proteins to colonize human tissues or to evade immune mechanisms for clearance of bacteria (Simpson-Louredo et al, 2014). Sabbadini et al (2010) suggested that the conversion of fibrinogen to fibrin may be connected to pseudomembrane formation, since differences in the abilities to bind and convert fibrinogen may partially explain differences in the extent of pseudomembrane formation during diphtheria.…”
Section: Discussionmentioning
confidence: 99%
“…The results were expressed in micrograms of adhered proteins, with a mean±SD of three independent assays, each performed in triplicate. The mean of the binding was compared by Tukey's multiple comparison test (Simpson-Louredo et al, 2014).…”
mentioning
confidence: 99%
“…Based on these genome sequences and comparative genomics approaches, a number of putative virulence factors were annotated; however, functional data were scarce. Up to now, data on fibrinogen, fibronectin and collagen binding, antimicrobial profiles, and arthritogenic potential of isolates have been published (Dias et al, 2011;Simpson-Louredo et al, 2014). In the study presented here, C. ulcerans 809 and BR-AD22 were characterized for the first time to the best of our knowledge with respect to adhesion to epithelial cells, invasion of epithelial cells and the function of two putative virulence factors in these initial processes of infection.…”
Section: Introductionmentioning
confidence: 89%
“…Up to now, data on adhesion and invasion of epithelial cells, fibrinogen, fibronectin and collagen binding, antimicrobial profiles and arthritogenic potential of isolates were published. [26][27][28] In the study presented here, C. ulcerans 809 and BR-AD22 were characterized for the first time to our knowledge in respect to their interaction with macrophages as important part of the innate immune system in order to get deeper insight into the pathogenicity of this emerging pathogen. The interaction with macrophages was of special interest, since the closely related animal pathogen Corynebacterium pseudotuberculosis, a facultative intracellular bacterium, is able to survive and grow in macrophages in order to disseminate within the host, 3,29 and also the human pathogen C. diphtheriae is able to survive within human macrophages.…”
Section: Introductionmentioning
confidence: 99%